Corruption Prevention Efforts with Non Penal Policy - Redyanto Sidi (Britain International for Academic Research (BIAR) Publisher, 2019)
This study discuss about the efforts of corruption prevention with non penal policy. Criminal politics as a rational effort of the community in tackling crime, can be carried out operationally either through reasoning facilities or nonpenal facilities. Penal and nonpenal means are a pair that cannot be separated from each other, it can even be said that they complement each other in an effort to deal with corruption. Some social problems and conditions which can be conducive factors for the emergence of crime are clearly problems that cannot be overcome alone eyes with reason.